Pan-Africanism and international law - Yusuf, Abdulqawi (Hague Academy of International Law, 2014)
Pan-Africanism offers a unique vantage point to study Africa's encounters with international law : first, as a continent whose political entities were excluded from the scope of application of the Eurocentric version of international law that was applied among the self-styled club of "civilized nations" ; second, through the emergence of African States as subjects of international law willing to contribute to the reform and further development of the law as a universal interstate normative system; and third, as members of the OAU and the AU acting collectively to generate innovative principles